2005
DOI: 10.1063/1.2130521
|View full text |Cite
|
Sign up to set email alerts
|

Roughness evolution in thin-film growth of SiO2 and Nb2O5

Abstract: Articles you may be interested inEffect of misfit strain and surface roughness on the tunable dielectric behavior of Ba 0.5 Sr 0.5 TiO 3 thin films

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
1
15
0
1
Order By: Relevance
“…It is thus expected that this anomalous scaling roughening could be caused by the limited surface diffusion mechanism. 26 Jeffries et al 19 found a similar result: they analyzed the roughening instability of Pt films sputtered at T s /T m ¼ 0.14 and proved that the limited diffusion mechanism resulted in the anomalous scaling (a ¼ 0.90 and b ¼ 0.26) of the films.…”
Section: Resultsmentioning
confidence: 60%
See 1 more Smart Citation
“…It is thus expected that this anomalous scaling roughening could be caused by the limited surface diffusion mechanism. 26 Jeffries et al 19 found a similar result: they analyzed the roughening instability of Pt films sputtered at T s /T m ¼ 0.14 and proved that the limited diffusion mechanism resulted in the anomalous scaling (a ¼ 0.90 and b ¼ 0.26) of the films.…”
Section: Resultsmentioning
confidence: 60%
“…Notably, we observed an upshift of G(r) as h s increased, suggesting that the sublayer roughening exhibits anomalous scaling. 26 We then obtained a by least-squares fitting to the linear slope of the logG(r)-logr plot at small r ((n). b is calculated from the R rms values, using the definition in Eq.…”
Section: Resultsmentioning
confidence: 99%
“…Larger growth exponents 0 5 β > . , as found experimentally in amorphous SiO 2 and Nb 2 O 5 thin films [8] as well as for instance in organic films [10,11], can be explained by including in the energies random fluctuations ( ) ε x which mimic the amorphous structure [5]. It was demonstrated in [5] for uniform white energy fluctuations ( ) ε x with…”
Section: The Kinetic Monte Carlo Modelmentioning
confidence: 90%
“…which follows from the saturation roughness sat w L α µ [8]. As we have shown previously [9] by setting ( ) 0, ε = x the basic model results in different growth regimes with growth exponents ranging from 0 .…”
Section: The Kinetic Monte Carlo Modelmentioning
confidence: 96%
“…One of the primary experimental goals is to achieve nanoscale control of layer thickness and surface morphology. For many thin film applications, for instance, in optics 25 or in semiconductor nanostructures, it is essential to control and adjust the roughness, e.g., in order to minimize scattering losses. On the theoretical side, considerable effort has been focused on developing suitable evolution equations for the growing layer.…”
mentioning
confidence: 99%